Biological compatibility between two temperate lineages of brown dog ticks, Rhipicephalus sanguineus (sensu lato) - Dantas-Torres, Filipe (Parasit Vectors, 2018)
BACKGROUND: The brown dog tick Rhipicephalus sanguineus (sensu stricto) is reputed to be the most widespread tick of domestic dogs worldwide and has also been implicated in the transmission of many pathogens to dogs and humans. For more than two centuries, Rh. sanguineus (s.s.) was regarded as a single taxon, even considering its poor original description and the inexistence of a type specimen. However, genetic and crossbreeding experiments have indicated the existence of at least two distinct taxa within this name: the so-called “temperate” and “tropical” lineages of Rh. sanguineus (sensu lato). Recent genetic studies have also demonstrated the existence of additional lineages of Rh. sanguineus (s.l.) in Europe and Asia. Herein, we assessed the biological compatibility between two lineages of Rh. sanguineus (s.l.) found in southern Europe, namely Rhipicephalus sp. I (from Italy) and Rhipicephalus sp. II (from Portugal). METHODS: Ticks morphologically identified as Rh. sanguineus (s.l.) were collected in southern Portugal and southern Italy. Tick colonies were established and crossbreeding experiments conducted. Morphological, biological and genetic analyses were conducted. RESULTS: Crossbreeding experiments confirmed that ticks from the two studied lineages were able to mate and generate fertile hybrids. Hybrid adult ticks always presented the same genotype of the mother, confirming maternal inheritance of mtDNA. However, larvae and nymphs originated from Rhipicephalus sp. I females presented mtDNA genotype of either Rhipicephalus sp. I or Rhipicephalus sp. II, suggesting the occurrence of paternal inheritance or mitochondrial heteroplasmy. While biologically compatible, these lineages are distinct genetically and phenotypically. CONCLUSIONS: The temperate lineages of Rh. sanguineus (s.l.) studied herein are biologically compatible and genetic data obtained from both pure and hybrid lines indicate the occurrence of paternal inheritance or mitochondrial heteroplasmy. This study opens new research avenues and raises question regarding the usefulness of genetic data and crossbreeding experiments as criteria for the definition of cryptic species in ticks. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-018-2941-2) contains supplementary material, which is available to authorized users.